Influence of melatonin on the development of functional nicotinic acetylcholine receptors in cultured chick retinal cells - Sampaio,L.F.S. (2005)
The influence of melatonin on the developmental pattern of functional nicotinic acetylcholine receptors was investigated in embryonic 8-day-old chick retinal cells in culture. The functional response to acetylcholine was measured in cultured retina cells by microphysiometry. The maximal functional response to acetylcholine increased 2.7 times between the 4th and 5th day in vitro (DIV4, DIV5), while the Bmax value for [125I]-alpha-bungarotoxin was reduced. Despite the presence of alpha8-like immunoreactivity at DIV4, functional responses mediated by alpha-bungarotoxin-sensitive nicotinic acetylcholine receptors were observed only at DIV5. Mecamylamine (100 µM) was essentially without effect at DIV4 and DIV5, while dihydro-ß-erythroidine (10-100 µM) blocked the response to acetylcholine (3.0 nM-2.0 µM) only at DIV4, with no effect at DIV5. Inhibition of melatonin receptors with the antagonist luzindole, or melatonin synthesis by stimulation of D4 dopamine receptors blocked the appearance of the alpha-bungarotoxin-sensitive response at DIV5. Therefore, alpha-bungarotoxin-sensitive receptors were expressed in retinal cells as early as at DIV4, but they reacted to acetylcholine only after DIV5. The development of an alpha-bungarotoxin-sensitive response is dependent on the production of melatonin by the retinal culture. Melatonin, which is produced in a tonic manner by this culture, and is a key hormone in the temporal organization of vertebrates, also potentiates responses mediated by alpha-bungarotoxin-sensitive receptors in rat vas deferens and cerebellum. This common pattern of action on different cell models that express alpha-bungarotoxin-sensitive receptors probably reflects a more general mechanism of regulation of these receptors.